Digital citizenship: Meta-analysis of research in Mexico - Diego René López Jacobo; Joel Angulo Armenta; Carlos Arturo Torres Gastelú (Universidad de Guadalajara, 2024)
The present study was a meta-analysis compiling research on digital citizenship conducted in Mexico in 2011 - 2023. It was guided by the objective of arguing, analyzing and categorizing the lines of knowledge generation and application (LGAC) related to digital citizenship in Mexico. The methodology applied was meta-analysis where 88 research studies were documented: 47 papers, 33 journal articles and 8 theses. The studies found support the existence of six LGAC in Mexico. It was concluded that the studies are related to understanding the way in which society appropriates digital technologies, interactions through social networks and the manifestations of digital identity. Another point to highlight is that the study of digital citizenship has been used to analyze the acquisition of digital skills and attitudes, social issues addressed by digitalization, the roles played by educational actors in the virtual environment and the promotion of multiculturalism. The studies found provide relevance to the LGAC, and allow concluding that digital citizenship is a topic present in research on educational technology in Mexico.